Evidence-based policymaking and the public interest: lessons in legitimacy. Issue 2 (13th March 2015) - McKay, Stephen; Murray, Michael; MacIntyre, Sean; Kashyap, Anil
Abstract : This paper draws upon an analysis of operational planning to highlight the centrality of ethics in praxis. In this context, political liberalism is particularly helpful in developing a deeper understanding of the activities of those engaged in planning decision making. At the most basic level, it demonstrates the importance of not only using shared liberal values as the foundation for public discourses, but also achieving consensus through the development of an inclusive evidence base, derived from both lay and professional knowledge. Though it has limitations, political liberalism provides a practical critique, enabling judgements to be made on problems which pervade operational planning practice and an evaluation to be conducted of the dynamic between, and actions of, participants.